Design of optimal waste heat recovery system for compressed air energy storage considering various system layouts and working fluid types - Xu Chen; Jian Li; Yunfei Zhang; Mingzhe Yu; Yujie Zhang; Xingying Chen; Jun Shen (Case Studies in Thermal Engineering, 2025)
Compressed Air Energy Storage (CAES) is a long-time electricity storage technology, whereas the low efficiency restricts its popularization. Recycling waste heat from interstage coolers can enhance performance of CAES, and organic Rankine cycle (ORC) shows good potential. Interstage coolers have multiple stages with different temperatures. Using the parallel ORC (PORC) potentially improves the recovery efficiency than the traditional single ORC (SORC). Meanwhile, the zeotropic mixture usually has a better thermodynamic performance but a poorer economic performance than common pure fluids. This paper studied the optimal scheme of ORC-based waste heat recovery system for CAES considering various system layouts and working fluid types. Single-objective optimization results show that using SORC will cause a 52.8 %–56.7 % increase in net present value while a 1.8 %–2.0 % decrease in net output power, compared to using PORC. Using zeotropic mixtures can achieve a 5.9 %–6.1 % increase in net output power and a 0.7 %–3.3 % increase in the net present value, compared to using pure fluids. Weighing thermodynamic and economic pursuits, the best design scheme is SORC with zeotropic mixtures, whose net output power and net present value are 2.74 MW and 5.29 × 106 $, respectively. Compared to without waste heat utilization, this scheme improves the efficiency by 4.0 % for CAES.